2018
DOI: 10.1101/341842
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive longitudinal microbiome analysis of the chicken cecum reveals a shift from competitive to environmental drivers and a window of opportunity for Campylobacter

Abstract: 21Chickens are a key food source for humans yet their microbiome contains bacteria that can be pathogenic to 22 humans, and indeed potentially to chickens themselves. Campylobacter is present within the chicken gut and 23 is the leading cause of bacterial foodborne gastroenteritis within humans worldwide. Infection can lead to 24 secondary sequelae such as Guillain-Barré syndrome and stunted growth in children from low-resource 25 areas. Despite the global health impact and economic burden of Campylobacter, ho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 53 publications
0
9
0
1
Order By: Relevance
“…Indeed, studies in mice with varying degrees of microbial imbalance prior to infection demonstrated that disturbed gut communities were more susceptible to infection by Salmonella enterica serovar Typhimurium 28 . Another study in chickens observed Campylobacter invasion of the cecal microbiome only after substantial changes to the metabolic profile were detected 29 . Direct interactions between the normal gut microbiota and invading pathogens via resource competition, metabolite production, and direct antagonism, coupled with the complexity of pathogen-induced inflammation, have also been shown to influence enteric infections 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies in mice with varying degrees of microbial imbalance prior to infection demonstrated that disturbed gut communities were more susceptible to infection by Salmonella enterica serovar Typhimurium 28 . Another study in chickens observed Campylobacter invasion of the cecal microbiome only after substantial changes to the metabolic profile were detected 29 . Direct interactions between the normal gut microbiota and invading pathogens via resource competition, metabolite production, and direct antagonism, coupled with the complexity of pathogen-induced inflammation, have also been shown to influence enteric infections 30 , 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence to support this transition has recently been reported in a study investigating daily changes in the caecal microbiota from 3 to 35 days of age and suggests that there is indeed a rapid evolution and increase in diversity in the caecal microbiota up to 12 days of age, this being driven by available space and food. 30 After 20 days of age the authors noted a stabilization in the microbiota in both diversity and abundance of species which was driven by the environmental conditions presented by each host chicken. In other words, the substrate and space available in the caeca were more or less constant after 20 days of age and hence the microbiota stabilizes into a structure best suited to the conditions which exist.…”
Section: Changes In the Microbiota As Governed By Changes In Nutrient...mentioning
confidence: 98%
“…It is clear from analysis of the caecal microbiota over time that there is a transition from species able to ferment starch, protein and many other sources of carbohydrate towards one which is almost exclusively targeting fibre fermentation. 25,[28][29][30] Readily fermentable carbohydrates such as starch and saccharides most often result in production of lactate in both the ileum and caecum, 31 whereas fibre tends to promote more of an acetate and butyrate fermentation in chickens. If this transition to fibre fermentation is too slow then it may increase the likelihood of an imbalance between fermentation of carbohydrate relative to protein and as a result a slide towards problems related to production of toxic products of putrefaction.…”
Section: Changes In the Microbiota As Governed By Changes In Nutrient...mentioning
confidence: 99%
See 1 more Smart Citation
“…kompleksowe, codzienne badania mikrobiomu kurcząt od 3 do 35 dnia życia ptaków wykazały, że Campylobacter pojawia się w 16 dniu życia, tuż po zaobserwowaniu najbardziej znaczących zmian w profilach metabolicznych. Nie można wykluczyć, że jest to wynik pojawienia się środowiskowych czynników stymulujących rozwój tych drobnoustrojów [41].…”
Section: Kampylobakterioza -źRódło Zakażeniaunclassified